Numerical study of a transient MHD flow across an oscillating vertical plate with thermal radiation and viscous dissipation - Rajaraman, Rengasamy; Muthucumaraswamy, Rajamanickam (Zielona Góra: Uniwersytet Zielonogórski)
The flow of an electrically conducting fluid across a vertically positioned oscillating semi-boundless plate with uniform mass diffusion and temperature is examined in this study in terms of the effects of thermal radiation and viscous dissipation. The dimensionless governing equations were solved using an effective and unconditionally stable implicit finite-difference approach known as the Crank-Nicolson method.
Keywords: MHD; finite-difference; thermal radiation; viscous dissipation; oscillating